Methimazole Inhibits the Expression of GFAP and the Migration of Astrocyte in Scratched Wound Model In Vitro - Lina Zhao; Xianyu Zhang; Chunhai Zhang (Hindawi Limited, 2020)
Astrocytes respond to central nervous system (CNS) insults with varieties of changes, such as cellular hypertrophy, migration, proliferation, scar formation, and upregulation of glial fibrillary acidic protein (GFAP) expression. While scar formation plays a very important role in wound healing and prevents further bleeding by forming a physical barrier, it is also one of key features of CNS injury, resulting in glial scar formation (astrogliosis), which is closely related to treatment resistant epilepsy, chronic pain, and other devastating diseases. Therefore, slowing the astrocytic activation process may give a time window of axonal growth after the CNS injury. However, the underlying mechanism of astrocytic activation remains unclear, and there is no effective therapeutic strategy to attenuate the activation process. Here, we found that methimazole could effectively inhibit the GFAP expression in physiological and pathological conditions. Moreover, we scratched primary cultures of cerebral cortical astrocytes with and without methimazole pretreatment and investigated whether methimazole could slow the healing process in these cultures. We found that methimazole could inhibit the GFAP protein expression in scratched astrocytes and prolong the latency of wound healing in cultures. We also measured the phosphorylation of extracellular signal-regulated kinase (ERK) in these cultures and found that methimazole could significantly inhibit the scratch-induced GFAP upregulation. For the first time, our study demonstrated that methimazole might be a possible compound that could inhibit the astrocytic activation following CNS injury by reducing the ERK phosphorylation in astrocytes.